Developing Pupils’ Creativity Through Integrated Lessons in The Primary Education - Egamberdiyeva Yulduz Urinboyevna (Web of Journals Publishing, 2023)
In this scientific article the author discusses about expanding pupils' creativity through integrated lessons in the primary education.
Keywords: Creativity, originality, imagination, expressiveness, self-confidence.